English Learning Needs of Accounting Students: A Basis for ESP Module Development - Marles Yohannis Matatula; Sophia Binnendyk; Hendrik Jacob Maruanaya (Huele: Journal of Applied Linguistics, Literature and Culture, 2026)
This study investigated the English learning needs of 55 accounting students at Pattimura University to inform the development of an ESP module. Data were collected through a structured questionnaire administered in Indonesian, covering learning objectives, self-reported proficiency, preferred topics, language task preferences, and exercise format preferences, and analyzed using frequencies and percentages. The findings revealed that academic purposes dominated students' learning motivations (49.1%), followed by career preparation (25.5%). Speaking emerged as the weakest skill, with the highest proportion of beginners (29.1%) and no advanced-level reporters, while reading showed the strongest profile (76.4% intermediate). Students preferred foundational business topics over specialized content and gravitated toward structured, scaffolded task formats such as summary writing, note completion, and contextual vocabulary gap-fill exercises. Based on these findings, the study proposes a five-unit module framework that maps empirically preferred topics and task types onto a scaffolded instructional sequence for ESP curriculum development at the institutional level.